Corporate strategies and profitability of maritime logistics firms - Parola, Francesco; Satta, Giovanni; Panayides, Photis (My University, 2015)
The inherent uncertainty, capital intensity and riskiness of investing in ships and port facilities have led to irregular corporate economic and financial performance for maritime logistics organizations. Although the relative impact of corporate strategy on firm profitability is a topic of considerable scientific and managerial interest, insights into contemporary issues in maritime logistics strategy are still limited. This article provides an exploratory contribution in bridging this gap, by measuring the effects of maritime logistics firm's corporate strategy on overall financial performance. Empirical findings show that investments for growth, focalization on the core business, related diversification and vertical integration have a positive impact on corporate profitability, whereas unrelated diversification does not affect firm's performance and international diversification has a negative effect. The outcomes are consistent with and add to the extant theoretical literature while insightful implications for research and practice are discussed.
Keywords: Corporate strategy; Diversification; Growth; Maritime logistics firms; Profitability